Sero-prevalence of Blood Borne Agents among Voluntary Blood Donors (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: Blood transfusion is a significant life-saving intervention in the present era of patient management system. As the blood and blood products are a potential source of infections and the necessity of transfusion is increasing day by day, transfusion transmissible infections have become a major threat to the system of ensuring safe transfusion.Objectives: To find out the sero-prevalence of Hepatitis B, Hepatitis C, HIV, Syphilis and Malaria parasite among the blood donors and to ascertain risk behaviour of the blood donors.Materials and Methods: This descriptive cross-sectional study was conducted on purposively selected 115 blood donors at Armed Forces Institute of Pathology (AFIP) during the period of 1st September to 31st December 2011.Results: The study revealed among 115 blood donors 7.8% were HBsAg positive. More than half of the HBsAg positive cases 66.67% were from civilian. None of the respondents was found positive for anti-HCV, VDRL, Malaria and anti-HIV. All of the donors in this study were voluntary donors. The sample studied had a mean age of 28.03 ± 6.79 years and 90.5% of donors were belongs to age group 18-37 years and female was only 6.1%. Most of the donors (49.5%) were military personnel,86%above SSC educated and 22.6% had visited abroad. Regarding risk behaviour 38.3% had the history of undertaking dental procedure, 0.9% were found undertaking blood transfusion, 2.6% had the history of illicit sex and 29.6% had the history of suffering from jaundice and among them only 1.7% were found HBsAg positive.Conclusion: The study finding demands motivation against unnecessary blood transfusion. It also emphasize health education programme among peoples having risk behaviour.Journal of Armed Forces Medical College Bangladesh Vol.15 (1) 2019: 71-74